Drivers of employees engagement for Eftra Group employees in TTDI Kuala Lumpur / Nurain Mohd Zuber - Mohd Zuber, Nurain (Faculty of Business and Management, 2009)
Employee engagement is a massive construct that touches almost all parts of management aspects we know up till now. If every part of the management is not addressed appropriately, employees could not engage themselves in their job in response to such kind of management.The main issue with employee engagement is that job hoping has become a common practice among employees these days and managers must take actions to defeat this issue. The percentage of job hopping in Malaysia will probably increase as majority of the country's workforce switches an average of three jobs in five years due to various reasons.In this study, the researcher has highlighted the main drivers for employee engagement based on Gallup Theory which are communication, management style, learning and development and lastly work environment. The study was using convenient sampling design with the sample size of 70 respondents with the population of 85 employees. The response rate is successfully 100% and the scales used to measure the findings are category scale and nominal scale.This paper aims at finding the underlying reasons on what drives employee to emotionally attach with their organization and highly participated in their job with excellent enthusiasm for the achievement of their employer, going further beyond the contractual agreement. As sum of all 70 employees from four divisions such media, creative ideas, builders and marketing were sampled for this study. It was found that the greatest degree of employee engagement was significantly driven by management style followed by work environment.Recommendations are provided for future researches references such that appreciation of hard work, shower praises, acknowledging their presence, give and take and strong team spirit encourage employee engagement eventually improve organization’s performance